CAPABILITIES OF AGRICULTURAL EXTENSION PERSONNEL TO TRANSFER CLIMATE CHANGE ADAPTATION TECHNOLOGIES TO FARMERS IN IMO STATE, NIGERIA - UMUNAKWE , P.C.; MADUKWE, M.C.; AJA, O.O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2022)
The increasing spate of climate change and its impacts on the economies of developing countries necessitate the undertaking of actions to reduce the adverse effects. This is particularly important for agriculture which is the major source of livelihood for many people in those areas. Hence, the study investigated the capabilities of agricultural extension personnel to transfer climate change adaptation technologies to farmers in Imo State, Nigeria. A sample of 130 agricultural extension personnel drawn from Imo State Agricultural Development Programme, using simple random sampling technique participated in the study. Data were collected using structured questionnaire and were analysed using mean scores and percentage. Results showed that the extension personnel were capable of transferring technologies on improved livestock breed/crop varieties ( = 3.4), SPAT ( = 3.4), promotion of environmentally-friendly agricultural practices ( = 3.2), training of farmers on weed/pest management ( = 3.2), and delivering instructions on application of agrochemicals (= 3.2). The personnel acquired capability for transfer of technologies through local seminars/workshops/conferences (95.7%), pre-service training (80.0%), routine in-house training (85.2%), internet (80.0%), journals and magazines (79.1%), training by non-governmental organizations (79.1%), and personal interaction with professional colleagues (79.1%). However, poor funding, ( = 3.5), inadequate manpower ( = 3.4), poor agricultural policies ( = 3.3), and inadequacy of required equipment ( = 3.3) constrained the acquisition of capabilities to transfer climate change technologies by the extension personnel. It was recommended, among others, that extension personnel should be equipped with the necessary skills required for effective transfer of climate change adaptation technologies.